Calcific aortic valve disease augments vesicular microRNA-145-5p to regulate the calcification of valvular interstitial cells via cellular crosstalk - Goody, Philip Roger; Christmann, D.; Goody, D.; Hildebrand, S.; Billig, H.; Nehl, D.; Chennupati, R.; Gladka, M.; Wilhelm-Jüngling, K.; Uchida, S.; Bibli, Sofia-Iris; Moore, J. B.; et al. (Basic research in cardiology, 2025)
Calcific aortic valve disease (CAVD) is one of the leading causes of cardiovascular death in the elderly population worldwide. MicroRNAs (miRNAs) are highly dysregulated in patients with CAVD undergoing surgical aortic valve replacement (SAVR). However, the miRNA-dependent mechanisms regulating inflammation and calcification or miRNA-mediated cell-cell crosstalk during the pathogenesis of CAVD remain poorly understood. Here, we investigated the role of extracellular vesicle (EV)-associated miR-145-5p, which we showed to be strongly upregulated in CAVD in mice and humans during valve calcification. Human TaqMan miRNA arrays identified dysregulated miRNAs in CAVD tissue explants from patients compared to non-calcified (patients with aortic insufficiency) heart valve tissue explants from patients undergoing SAVR. Echocardiographic parameters were measured in conjunction with the quantification of dysregulated miRNAs in a murine CAVD model. In vitro calcification experiments were performed to investigate the effects of EV-miR-145-5p on calcification and crosstalk in heart valve cells. Integrated OMICS analyses were performed to analyze molecular miRNA signatures and their effects on signaling pathways-associated with CAVD. RNA sequencing, high-throughput transcription factor (TF) activity assays, and osteogenesis arrays revealed that a number of genes, miRNAs, TFs are critical for calcification and apoptosis involved in the pathogenesis of CAVD. Among several miRNAs dysregulated in valve explants from CAVD patients, miR-145-5p was the most highly sex-independently upregulated miRNA (AUC, 0.780, p value, 0.01) in patient plasma. Large EV population (170-800 nm) isolated from aortic valve tissues explanted from patients with CAVS (calcific aortic valve stenosis) after SAVR demonstrated a significantly higher level of miR-145-5p expression in comparison to control (vesicle-free plasma). MiRNA arrays utilizing with aortic stenosis samples from patients and mice showed that the expression of miR-145-5p is significantly upregulated and positively correlated with cardiac function based on echocardiography. In vitro experiments confirmed that miR-145-5p is encapsulated in EVs and transported into interstitial cells of the aortic valve. The results of integrated OMICs show that miR-145-5p is related to markers of inflammation, calcification, and apoptosis. In vitro calcification experiments demonstrated that miR-145-5p regulates the ALPL gene, a hallmark of calcification in vascular and heart valve cells. Mechanistically, EV-mediated shuttling of miR-145-5p suppressed the expression of ZEB2, a negative regulator of the ALPL gene, by binding to its 3' untranslated region to inhibit its translation, thereby diminishing the calcification of valvular interstitial cells. Elevated levels of pro-calcific and pro-apoptotic EV-associated miR-145-5p contribute to the progression of CAVD via the ZEB2-ALPL axis, which could potentially be therapeutically targeted to minimize the burden of CAVD. Graphical abstract